GENERAL CHARACTERISTICS OF TYPES OF CONTRACTS CONCLUDED IN TRADE TURNOVER - Amosov, Artur A.; Naumova, Tatyana Y.; Kononov, Alexey N. (Russian studies in law and politics, 2023)
The system of civil contracts in the Russian Federation is of great importance for practice and is the subject of many years of detailed study of Russian legal science. The classification of contracts in civil law still causes controversy and debate among scientists, and so far no one has been able to propose a universal classification. The situation with the classification of contracts in the trade turnover of the Russian Federation is also difficult. Even the identification of such a category and this name raises questions and creates various opposing points of view among scientists. Indeed, in any textbook on corporate and trade law of the Russian Federation it is very difficult to find the term agreement in trade turnover, as well as to distinguish the types of such agreements. More and more often we come across concepts such as a commercial agreement or a trade agreement, however, such concepts should not be fully identified, although they have similar features. Perhaps there cannot be a uniform and accurate classification due to the fact that contract law is a very dynamically developing industry, which is constantly changing from a practical point of view, and practice, as we know, acts and does not think about fitting into the usual format, theories and classifications. In this article, a team of authors provides a unique systematization of the types of contracts used in trade turnover on the territory of the Russian Federation, analyzes and characterizes and assesses the relevance of various forms of concluding commercial contracts, and also highlights the prospects for the development of national contract law, which functions and is the most important component of trade turnover.